A recent increase in the abundance of the echinoid Diadema antillarum in Dominica (Lesser Antilles): 2001-2005 - Steiner, S. C. C. (2006)
Diadema antillarum populations at many Caribbean locations have failed to recover from the pathogen- induced mortality events of the 1980s. It has become clear that the massive decline of this herbivorous urchin and the wide-spread absence of a population recovery lead to numerous long-term ecological consequences and reef degradation. While few quantitative studies on pre-mortality exist, great effort has been put forth to monitor remaining populations and their recovery. However, the patchy distribution of D. antillarum coupled with paucity of long-term studies based on the same methods applied at the same locations undermines the value of local as well as regional comparisons. In Dominica, ongoing quantitative assessments of D. antillarum began in 2001. Surveys of D. antillarum abundance are being carried out in 4-month intervals at six 100 m2 sites; spread over 38 km along the west coast. The density of D. antillarum has differed significantly between sites, ranging from 0.81 (SD=0.04) to 3.13 m-2 (SD=2.10), and increased by 61.11% during the first five years of this study. Seasonal fluctuations, possibly related to spawning aggregations, are also evident. The current abundance of D. antillarum on Dominican reefs contrasts that of Caribbean locations with recorded incidents of mass mortality events, and in some cases resembles pre-mortality densities from the early 1970s. Prior to this study, no systematic quantitative assessments of D. antillarum were carried out in Dominica. It is thus unclear in what way Dominica’s D. antillarum were affected by the mass mortality events observed elsewhere in the 1980s. The increase in D. antillarum density so far observed may thus be the recovery from a pathogeninduced disturbance or from Hurricane Lenny in November 1999. Locally, D. antillarum is important grazer on Dominican’s reefs, where over-fishing has drastically reduced the number of herbivorous fishes. On a regional scale, the island’s D. antillarum may represent a source of larvae for downstream islands, given the duration of the echinoplutei stage and a range of larval dispersal of hundreds of kilometers. Rev. Biol. Trop. 54 (Suppl. 3): 97-103. Epub 2007 Jan. 15.